2002
DOI: 10.1038/sj.jhh.1001379
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria is associated with unfavourable cardiac geometric adaptations in essential hypertensive subjects

Abstract: We sought in this study to examine the relationship between microalbuminuria and cardiac geometry since a slight increased urinary albumin excretion (UAE) and increased left ventricular (LV) mass have both been identified as predictors of cardiovascular events in hypertensive subjects. For this purpose, microalbuminuria was determined in three non-consecutive 24-h urine samples as UAE of 20-200 mg/24 h in a group of 249 untreated hypertensive subjects. Echocardiographic classification of patients into LV geome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
12

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 25 publications
4
20
0
12
Order By: Relevance
“…Recent reports have evidenced that in essential hypertension, patients with high-normal albuminuria had a greater RWT and more frequent concentric left ventricular hypertrophy, 24 and that the prevalence of concentric left ventricular hypertrophy was significantly higher in microalbuminuric compared with normoalbuminuric subjects. 25 Our data suggest that concentric geometry in mild GH women might be linked to the occurrence of proteinuria, because 12 out of the 14 patients with preeclampsia had a concentric geometry before its appearance.…”
Section: Discussionmentioning
confidence: 64%
“…Recent reports have evidenced that in essential hypertension, patients with high-normal albuminuria had a greater RWT and more frequent concentric left ventricular hypertrophy, 24 and that the prevalence of concentric left ventricular hypertrophy was significantly higher in microalbuminuric compared with normoalbuminuric subjects. 25 Our data suggest that concentric geometry in mild GH women might be linked to the occurrence of proteinuria, because 12 out of the 14 patients with preeclampsia had a concentric geometry before its appearance.…”
Section: Discussionmentioning
confidence: 64%
“…[29][30][31][32][33][34] In contrast, the independent cardiovascular prognostic role of SUA is still debatable since in the majority of studies it is suggested that it might be the result of complex interactions with other well-defined risk markers. In line with the previous data, Alderman et al 35 found that SUA levels were positively associated with future cardiovascular adverse events in patients with essential hypertension, although this association was not statistically significant in both the white population and in subjects without a history of previous cardiovascular disease.…”
Section: Uric Acid and Target Organ Damage C Tsioufis Et Almentioning
confidence: 99%
“…1 Moreover, the association between UAE and increased CVD mortality in high-risk groups begins at levels of UAE below clinically defined thresholds for microalbuminuria. 1 Subclinical CVD, such as left ventricular (LV) hypertrophy [2][3][4][5][6] and increased carotid artery intima-media thickness (IMT), [7][8][9][10][11][12] has been associated with microalbuminuria among individuals at high risk for CVD. Whether the presence of increased UAE provides any additional predictive value for the presence of subclinical CVD in groups not at high risk aside from established, independent CVD risk factors remains unestablished.…”
mentioning
confidence: 99%